Investigating The Impact Of Net Technologies On The Effectiveness Of Sme's - Analytical Study- - Boukeffa Hamza (جامعة الوادي University of Eloued, 2024)
This paper aims to illustrate how the implementation of Network Technologies (Net-Techs) impact the effectiveness of small and medium enterprises in Algeria. It examines the way Net-Techs allow small and medium enterprises to enhance their productivity, reorganize human resources management and information systems, regulate competitive forces, lower expenses, effectively manage information and knowledge, enhance internal and external communication, facilitate decision-making, enter new markets, and boost their revenue. For small and medium-sized enterprises to effectively utilize network technology, several prerequisites must be fulfilled. The prime requirement is the integration of information technology and communications as a fundamental part of their overall strategy. Additionally, it is crucial to cultivate experts in information technology and communications, consistently enhance and modernize their applications, ensure accessibility for all members of the enterprise, and implement organizational adjustments and changes that align with the enterprise's new position.
Keywords: Net technologies; effectiveness; small and medium enterprises; information system.